Monitoring of Masjed-Soleiman embankment dam’s deformation using a combination of Interferometric Synthetic Aperture Radar (InSAR) and finite element modeling - Aminjafari, Saeed (Geodesy and Cartography, 2017)
The fresh water shortage is one the most important challenges in many countries like Iran. So there have been incentives to manipulate and manage water resources by constructing dams. Clay core embankments are one of the most popular dam structures. A layer of clay can be a reliable obstacle in front of water stream. However, because of the soil’s nature, these kinds of dams have the potential of instability. Thus deformation of clay core dams should be monitored frequently. The aim of this study is to use the combination of Interferometric Synthetic Aperture Radar technique (InSAR) and Finite Element Modeling (FEM) for dam’s deformation monitoring. For the InSAR analysis we used data from ENVISAT sensor and processed those using Small BAseline Subset (SBAS). We show that InSAR is an invaluable approach to monitor clay core dam’s deformation in specific circumstances. The deformation derived from InSAR was used as an initial condition in Finite Element Modeling. The case study is Masjed Soleiman Dam which is situated in South West of Iran. We used 19 ASAR images of ENVISAT sensor from 2003/8/22 to 2010/5/7. The process of ASAR images showed maximum velocity of 11 mm/year in LOS direction at central lower areas of dam. These results were compared with Geodetic Surveying Operations at four points on dam and the average agreement of 77 percent was obtained. The results of ENVISAT data have a good consistency with FEM results. Horizontal and vertical displacements derived from instrumentations and modeling are plotted versus depths. There is a good agreement between modeling results and instrumentations data.